베트남 외국인 근로자의 문화적응 스트레스와 우울 - 전혜정(Hye Jeong Jeon); 이가언(Ga Eon Lee) (지역사회간호학회지, 2015)
Purpose: The purpose of this study was to investigate the correlation between acculturative stress and depression of Vietnamese immigrant workers in Korea. Methods: The subjects were 230 Vietnamese immigrant workers residing legally in B or K City. Data were collected from July 12, 2014 to August 3, 2014, and were analyzed using the SPSS PASW 21.0 program. Results: The average level of acculturative stress was 2.91 and there were significant differences in the score according to whether to have a religion, the number of homeland friends, and Korean language skill. The average depression level of the subjects was 15.3 and the level was different significantly according to whether to have a religion, the number of homeland friends, salary, working hours, and Korean language skill. Acculturative stress and depression showed a significant positive correlation with each other. The influencing factors of depression were acculturative stress and the number of homeland friends. The most significant factor was acculturative stress. Conclusion: This result shows the necessity of various programs to diminish acculturative stress to control the depression of immigrant workers.